Chapter 12 DISABLED CHILDREN'S PARTICIPATION IN HEALTHCARE DECISION-MAKING - Keravica, Rados (Taylor & Francis, 2023)
Disabled children are exposed to a host of remedial treatments, therapies or surgeries seeking to restore the 'normality' of their bodies and minds. The Convention on the Rights of the Child (CRC) in its Article 12 entitles children with the 'right to be heard' in all matters that affect their lives including healthcare. This chapter explores the barriers to participation disabled children may face in the context of healthcare decision-making and examines the synergies between the norms of the CRC and the Convention on the Rights of Persons with Disabilities (CRPD) setting standards for States Parties to eliminate such barriers.